In-Lab Upfront Use of Tirofiban May Reduce the Occurrence of No-Reflow During Primary Percutaneous Coronary Intervention. A Pilot Randomized Study - Lago,Igor Matos (2016)
Abstract Background: Despite successful opening of culprit coronary artery, myocardial reperfusion does not always follows primary percutaneous coronary intervention (PPCI). Glycoprotein IIb/IIIa inhibitors are used in the treatment of no-reflow (NR), but their role to prevent it is unproven. Objective: To evaluate the effect of in-lab administration of tirofiban on the incidence of NR in ST-elevation myocardial infarction (STEMI) treated with PPCI. Methods: STEMI patients treated with PPCI were randomized (24 tirofiban and 34 placebo) in this double-blinded study to assess the impact of intravenous tirofiban on the incidence of NR after PPCI according to angiographic and electrocardiographic methods. End-points of the study were: TIMI-epicardial flow grade; myocardial blush grade (MBG); resolution of ST-elevation < 70% (RST < 70%) at 90min and 24h after PPCI. Results: Baseline anthropometric, clinical and angiographic characteristics were balanced between the groups. The occurrence of TIMI flow < 3 was not significantly different between the tirofiban (25%) and placebo (35.3%) groups. MBG ≤ 2 did not occur in the tirofiban group, and was seen in 11.7% of patients in the placebo group (p=0.13). RST < 70% occurred in 41.6% x 55.8% (p=0.42) at 90min and in 29% x 55.9% (p=0.06) at 24h in tirofiban and placebo groups, respectively. Severe NR (RST ≤ 30%) was detected in 0% x 26.5% (p=0.01) at 90 min, and in 4.2% x 23.5% (p=0.06) at 24h in tirofiban and placebo groups, respectively. Conclusion: This pilot study showed a trend toward reduction of NR associated with in-lab upfront use of tirofiban in STEMI patients treated with PPCI and paves the way for a full-scale study testing this hypothesis.